2022
DOI: 10.1039/d2en00450j
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of photoinduced toxicity of AgNPs to the microalgae Chlorella pyrenoidosa in the presence of hematite nanoparticles: insights from transcriptomics, metabolomics and the photochemical index

Abstract: Silver nanoparticles (AgNPs) have little impact on organisms at environmentally relevant concentrations. However, AgNPs coexisting with photoactive minerals may show an elevated combined ecotoxicity due to the additional photoinduced cytotoxicity...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Photocatalytic materials can generate free radicals in aquatic environments under visible light irradiation, leading to adverse effects on aquatic microorganisms. Studies have shown that toxicity is positively correlated with the generation of free radicals. , Our previous research has also demonstrated that free radicals induce phototoxicity in algae . The EIS, PC, and EPR results provided direct evidence that ZnO NPs could promote the phototransformation of DOP.…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…Photocatalytic materials can generate free radicals in aquatic environments under visible light irradiation, leading to adverse effects on aquatic microorganisms. Studies have shown that toxicity is positively correlated with the generation of free radicals. , Our previous research has also demonstrated that free radicals induce phototoxicity in algae . The EIS, PC, and EPR results provided direct evidence that ZnO NPs could promote the phototransformation of DOP.…”
Section: Resultsmentioning
confidence: 77%
“…There are numerous reports indicating that P deficiency, coupled with the presence of nanoparticles, induces the overproduction of ROS, resulting in cytotoxic effects. The results showed that the P-free group produced the most ROS (Figure C). In addition, more ROS were produced in the DOP groups than in the K 2 HPO 4 group, suggesting that the algae were less able to utilize DOP, causing more severe P starvation.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…However, this effect is more often a result of the stress caused by high concentrations of these nanoparticles. At the current stage, the greatest successes in the study of the interactions between nanoparticles and microalgae pertain to elucidating these entities' toxicity mechanisms, with the metabolic pathways involved in the response reactions being highlighted [13]. At the same time, by applying low concentrations of nanoparticles, it is possible to accelerate the growth rate of microalgae, improve nutrient absorption, stimulate biomass production, and optimize the synthesis of bio-products of interest, such as proteins, carbohydrates, pigments, and lipids [8,14,15].…”
Section: Quantity Of P Purpureum Cnmn-ar-02 Biomass Produced Under Cu...mentioning
confidence: 99%